Facteurs et conséquences de la déficience de la stratégie de gouvernance au Maniema dans le contexte du régionalisme politique de 2007 à 2015 - Morisho, Adolphe Ndokili (IJRDO - Journal of Business Management, 2021)
This reflection aims to identify the factors of the deficiency of the governance strategy in the Maniema, in the context of the political regionalism and to clear the consequences that ensue some. Indeed, several factors explain the deficiency of the governance strategy to the Maniema. There are the exogenous factors and the endogenous factors. The exogenous factors, we have the factors of political, legal, economic and financial order.The endogenous factors, are: the factors political, administrative, economic, human as well as the sociocultural factors. Several consequences ensue of this deficiency, notably the consequences of political, economic, financial and social order. Being about the consequences of political order, our investigatings cleared: the délegitimation of the governing; the weak adherence of governed them to the politics of governing and the non appropriation of the actions of the provincial Government by the actors of the private sector and the civil society as well as the resurgence of the armed movements and the upsurge of the insecurity through the province.For the consequences of economic and financial order, we cleared: the accentuation of poverty and the deterioration of the economic infrastructures and the factors of production. With regard to the consequences of sociocultural order, the results of our investigations reveal the difficult access to the sanitary services, to the drinking water and to electricity; the precariousness of the habitat; the difficult access to the school service to the deficit of the social protective system.